Ppia is the most stable housekeeping gene for qRT-PCR normalization in kidneys of three Pkd1-deficient mouse models - Juan J. Muñoz (Nature Portfolio, 2021)
Abstract Autosomal Dominant Polycystic Kidney Disease (ADPKD) is the most common inherited renal disorder, characterized by renal cyst development leading to end-stage renal disease. Although the appropriate choice of suitable reference is critical for quantitative RNA analysis, no comparison of frequently used “housekeeping” genes is available. Here, we determined the validity of 7 candidate housekeeping genes (Actb, Actg1, B2m, Gapdh, Hprt, Pgam1 and Ppia) in kidney tissues from mouse models orthologous to ADPKD, including a cystic mice (CY) 10–12 weeks old (Pkd1 flox/flox:Nestin cre/Pkd1 flox/−:Nestin cre, n = 10) and non-cystic (NC) controls (Pkd1 flox/flox/Pkd1 flox/-, n = 10), Pkd1-haploinsufficient (HT) mice (Pkd1 +/−, n = 6) and wild-type (WT) controls (Pkd1 +/+, n = 6) and a severely cystic (SC) mice 15 days old (Pkd1 V/V, n = 7) and their controls (CO, n = 5). Gene expression data were analyzed using six distinct statistical softwares. The estimation of the ideal number of genes suggested the use of Ppia alone as sufficient, although not ideal, to analyze groups altogether. Actb, Hprt and Ppia expression profiles were correlated in all samples. Ppia was identified as the most stable housekeeping gene, while Gapdh was the least stable for all kidney samples. Stat3 expression level was consistent with upregulation in SC compared to CO when normalized by Ppia expression. In conclusion, present findings identified Ppia as the best housekeeping gene for CY + NC and SC + CO groups, while Hprt was the best for the HT + WT group.